Pengaruh Brand Experience, Price, terhadap Customer Satisfaction dan Customer Loyalty Pengguna Smartphone Oppo - Fajar Swantantra Nata; Unik Dwi Lestari (Transformasi: Journal of Economics and Business Management, 2024)
The rapid development of information and communication technology has caused significant changes to people's lives, especially in terms of communication. People's needs in this era of globalization in the form of smartphones are high because technology continues to experience development. This study aims to determine the effect of Brand Experience, Price and Customer Satisfaction, on Oppo Smartphone Customer Loyalty. In this study, the population studied was all people who bought and used an Oppo smartphone. The sample in this study amounted to 200 people using a purposive sampling technique. The data is then processed using the Lisrel Structural Equation Model (SEM) method. Based on the test results, it is known that Brand Experience has an effect on Customer Satisfaction. Price has no effect on Customer Satisfaction. Brand Experience has no effect on Customer Loyalty. Price has an effect on Customer Loyalty. Customer Satofaction has no effect on Customer Loyalty.